2020
DOI: 10.3390/v12101102
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Exogenous Trypsin Expands In Vitro Cellular Tropism of the Avian Coronavirus Infectious Bronchitis Virus

Abstract: The Gammacoronavirus infectious bronchitis virus (IBV) causes a highly contagious and economically important respiratory disease in poultry. In the laboratory, most IBV strains are restricted to replication in ex vivo organ cultures or in ovo and do not replicate in cell culture, making the study of their basic virology difficult. Entry of IBV into cells is facilitated by the large glycoprotein on the surface of the virion, the spike (S) protein, comprised of S1 and S2 subunits. Previous research showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…On the contrary, the 19 independent studies that we reviewed ( Table S1 ) consistently showed that exogenous trypsin added to host cells in presence of SARS-CoV-1 ( n = 3), SARS-CoV-2 ( n = 10) and other coronaviruses ( n = 7) does not annihilate nor stop, but facilitates priming of the spike and/or cell entry, and enhances virus infectivity, cell fusion and syncytia formation in vitro [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The effects were obtained in the ng to µg trypsin/mL range, so likely at lower (and thus relevant) concentrations than obtained with the 1.2 mL volume used in the manufacturer’s virucidal suspension test.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the contrary, the 19 independent studies that we reviewed ( Table S1 ) consistently showed that exogenous trypsin added to host cells in presence of SARS-CoV-1 ( n = 3), SARS-CoV-2 ( n = 10) and other coronaviruses ( n = 7) does not annihilate nor stop, but facilitates priming of the spike and/or cell entry, and enhances virus infectivity, cell fusion and syncytia formation in vitro [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The effects were obtained in the ng to µg trypsin/mL range, so likely at lower (and thus relevant) concentrations than obtained with the 1.2 mL volume used in the manufacturer’s virucidal suspension test.…”
Section: Resultsmentioning
confidence: 99%
“…The effects were obtained in the ng to µg trypsin/mL range, so likely at lower (and thus relevant) concentrations than obtained with the 1.2 mL volume used in the manufacturer’s virucidal suspension test. Table S1 summarizes detailed information on the assays and methods applied, and the key findings of the studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Virus resistance to trypsin, virus survival and enhanced or sustained cell invasion and syncytia formation with trypsin were also reported in host cell assays with rhinovirus, RSV and influenza [ 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations